2016
DOI: 10.1093/jme/tjw164
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sampling Methods for Sarcosaprophagous Species and Other Guilds of Calyptratae (Diptera) in Temperate Forests of Southern South America

Abstract: The aim of the present study was to compare three different collecting methods, namely, baited traps, active capture with hand net, and Malaise traps, to establish which method is more appropriate for sampling different Calyptratae guilds inhabiting temperate forests of South America. Specifically, it was analyzed which technique or combination of techniques is more adequate for obtaining sarcosaprophagous Calyptratae, which are of great interest from a veterinary and medical viewpoint. Taxa were classified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…These captures were done for one to three hours by one to three collectors. Despite this method is a highly collector-dependent method (depending on his ability and expertise to capture flies) and not easily replicable, previous comparisons between collecting methods to establish which one is more appropriate for sampling different Calyptratae guilds demonstrated that active capture by highly trained collectors was the most reliable practice to obtain kleptoparasites (Olea et al, 2017).…”
Section: Samplingmentioning
confidence: 99%
“…These captures were done for one to three hours by one to three collectors. Despite this method is a highly collector-dependent method (depending on his ability and expertise to capture flies) and not easily replicable, previous comparisons between collecting methods to establish which one is more appropriate for sampling different Calyptratae guilds demonstrated that active capture by highly trained collectors was the most reliable practice to obtain kleptoparasites (Olea et al, 2017).…”
Section: Samplingmentioning
confidence: 99%
“…Sampling was conducted for two consecutive years, 2014 and 2015, during the warmer, humid summer and colder, dry winter seasons. Adult flies were collected at each site with two traps exposed to different insolation conditions, sunlight and shade (total number of traps 26) baited with 200 g of hydrated bone meal (putrescine) (Olea et al, 2017), and hung with a cord from a pole or tree branch 1.5-2 m from the ground and at the shelter of the wind. The traps were adapted from Hwang & Turner (2005) and are described in detail in Battán-Horenstein et al (2016).…”
Section: Study Area and Sampling Proceduresmentioning
confidence: 99%
“…Compared to other saprophagous families, relatively little is known about the ecology of Neotropical sarcophagids. In Argentina, studies of Sarcophagidae inhabiting urban environments have only been performed in Buenos Aires and its surrounding areas, characterized by a humid subtropical climate without a dry season (Köppen‐Geiger climate classification: Cfa) (Mulieri et al ., 2011; Patitucci et al ., 2015), and in the southeast of Patagonia, characterized by a cold semidesert climate (Köppen‐Geiger classification: BWk) (Olea et al ., 2017). To our knowledge, there is little published information about the fauna and ecology of the Sarcophagidae in Central Argentina, where the climate is humid subtropical with dry winters (Köppen‐Geiger classification: Cwa).…”
Section: Introductionmentioning
confidence: 99%
“…(), amongst other. In addition, researchers have been investigating the diversity and seasonal dynamics of some saprophagous flies using different types of bait (Mulieri et al ., ; Patitucci et al ., ; Battán‐Horenstein et al ., ; Dufek et al ., ; Olea et al ., ). Differences in the performance of baited traps indicate that the type of decomposing organic matter can affect the assembly of species that are attracted, which could be expected because they may differ in terms of both their nutrient composition and their physical and chemical properties (Hanski, ).…”
Section: Introductionmentioning
confidence: 97%